Impact of the coronavirus disease 2019 (COVID-19) pandemic on tumor stage progression in urological malignancies: a comparative study - Keskin, Alper; Yorulmaz, Enis Mert; Donmez, Kursad; Ozcan, Serkan; Kose, Osman; Gorgel, Sacit Nuri; Akin, Yigit (Frontiers in Urology, 2025)
ObjectiveTo determine whether delays in care during the coronavirus pandemic 2019 (COVID-19) were associated with pathological stage progression in urological malignancies by comparing surgical outcomes between pre-pandemic era (PREP) and pandemic-era (POSTP) cohorts.MethodsWe conducted a retrospective before-and-after cohort study at a tertiary academic center. A total of 368 patients underwent radical surgeries for prostate (n=176), bladder (n=78), kidney (n=78), or testicular (n=36) cancers between April 2019 and March 2022. Patients were grouped into PREP (April 2019–March 2020) and POSTP (April 2020–March 2022) cohorts. Clinical, laboratory, and pathological data were compared using Student’s t-test, Mann–Whitney U test, Chi-square test, or Fisher’s exact test, with p<0.05 considered statistically significant.ResultsPOSTP prostatectomy patients had significantly higher preoperative PSA levels (13.2 ± 16.2 vs. 7.7 ± 4.5 ng/mL, p<0.001), greater tumor involvement (17.0% vs. 11.5%, p=0.019), and increased extraprostatic extension (33.7% vs. 11.9%, p=0.006) compared to PREP patients. Renal tumors were significantly larger during the pandemic (7.4 cm vs. 6.0 cm, p=0.01), and preoperative hemoglobin levels were lower (11.7 vs. 12.9 g/dL, p<0.001), suggesting more advanced disease. No statistically significant differences were observed in pathological staging for bladder or testicular cancers between the two periods (all p>0.05).ConclusionCOVID-19-related care disruptions were associated with adverse pathological features in prostate and renal cancers. In contrast, bladder and testicular cancers showed no significant stage migration. These findings emphasize the need for resilient cancer care pathways to prevent progression during future healthcare crises.